The Role of Social Media and E-Commerce in Accelerating the Growth of Indonesian MSMEs - Samsudin, Samsudin (International Conference on Sciences Development and Technology, 2023)
Advances in digital technology and the internet have changed the way Micro, Small and Medium Enterprises (MSMEs) in Indonesia market and distribute their products. This study analyzes the role of social media and e-commerce in supporting the growth of MSMEs. The results of the study show that the use of social media such as Instagram and TikTok can increase brand awareness by up to 70%, while e-commerce platforms such as Shopee and Tokopedia provide access to a wider market and improve operational efficiency. While many MSMEs face challenges such as limited digital knowledge and resources, collaboration between governments, the private sector, and educational institutions can be a strategic solution to overcome these barriers. This research recommends optimizing digital media through data-driven strategies and partnerships with local platforms to accelerate the growth of MSMEs in the digital era.